Comparative study of stability models for identifying stable spring wheat genotypes in diverse conditions - Vijay Kamal Meena; Ram Kumar Sharma; Subhash Chand; Shahil Kumar; Kapil Choudhary (Discover Agriculture)
Abstract To assess the agronomic performance and genetic stability for grain yield, a set of 36 spring wheat genotypes were grown consecutively for two crop seasons in six environments with varying sowing dates at ICAR-Indian Agricultural Research Institute, New Delhi using randomized complete block design with three replications. Significant genotypic differences were observed for all the studied morpho-physiological characters in both the crop seasons suggesting the presence of substantial genetic variability among the genotypes studied. Parametric and nonparametric stability analysis methods, along with advanced techniques like AMMI and GGE biplot analysis, were employed to understand genotype-environment interactions. Positive correlations were found between yield and stability parameters, highlighting the importance of selecting genotypes with both high yield and stability. Based on the wide-ranging evaluations, three out of 36 genotypes viz., DW1615, HD3262, and DW1631, emerged most promising ones consistently demonstrated superior performance across multiple methodologies. The study underscores the need to follow a multifaceted approach for genotype evaluation to ensure sustainable improvement in wheat production systems, enabling breeders to make informed decisions for resilience and productivity in diverse/varying environmental conditions.